Knowledge of and attitude to foot care amongst type 2 diabetes patients attending a university-based primary care clinic in Nigeria (2010)
Background: Individuals living with diabetes mellitus are at an increased risk of developing foot ulcers and cardiovascular complications or a neuropathy that may result in amputations. These complications have been shown to be already present in about 10% of diabetic patients at the time of diagnosis. Objectives: This study was carried out to determine the level of awareness and attitude to foot care among adult diabetic patients attending a university health centre (i.e. a primary care centre) and to emphasise the ever-present need for health education and promotion and early complication detection (especially of foot problems) among diabetic patients. Method: A descriptive cross-sectional, clinic-based study was carried out at the University of Ibadan Health Centre (Jaja Clinic). The study population consisted of consenting adult diabetic patients. Data were collected by the self-administration of structured questionnaires to eligible subjects and were analysed using the SPSS v.15software. Appropriate statistics were employed to analyse the collected data. Results: A total of 137 patients participated in the study and ranged in age from 37 to 75 years, with the mean ± SD age being 58.2 ± 9.2 years. Of the participants, 98 (71.5%) were men and 39 (28.5%) were women; all of the participants were married. The duration of illness ranged from 1 year to 20 years, with the median duration of illness being 3 ± 1.7 years. One hundred and twenty-six (92%) patients had never received any education on foot care from their healthcare providers, while 11 (8%) had received some form of foot care education. Among those who had never received any foot care education, 92 (73%) had been diabetic for 1–5 years, while the remaining 34 (27%) had been diabetic for 6 – 20 years. Of the foot care measures that were known, 35 (25.5%) patients knew to wash their feet daily and dry in between the toes thoroughly, 31 (22.6%) knew not to go outdoors barefooted, 27 (19.7%) checked their feet daily, 27 (19.7%) checked inside their shoes daily, 8 (5.8%) consciously made an effort to avoid injuries to their feet and 4 (2.9%) clipped their toenails with care. Conclusion: The results of this study showed that awareness of foot care measures is very poor among known diabetic patients and this is largely due to a lack of education of the patients by their health care providers.